Astrocyte Reprogramming in Stroke: Opportunities and Challenges - Peng, Zhouzhou; Lu, Hui; Yang, Qingwu; Xie, Qi (Frontiers in Aging Neuroscience, 2022)
Stroke is a major cause of morbidity and mortality worldwide. In the early stages of stroke, irreversible damage to neurons leads to high mortality and disability rates in patients. However, there are still no effective prevention and treatment measures for the resulting massive neuronal death in clinical practice. Astrocyte reprogramming has recently attracted much attention as an avenue for increasing neurons in mice after cerebral ischemia. However, the field of astrocyte reprogramming has recently been mired in controversy due to reports questioning whether newborn neurons are derived from astrocyte transformation. To better understand the process and controversies of astrocyte reprogramming, this review introduces the method of astrocyte reprogramming and its application in stroke. By targeting key transcription factors or microRNAs, astrocytes in the mouse brain could be reprogrammed into functional neurons. Additionally, we summarize some of the current controversies over the lack of cell lineage tracing and single-cell sequencing experiments to provide evidence of gene expression profile changes throughout the process of astrocyte reprogramming. Finally, we present recent advances in cell lineage tracing and single-cell sequencing, suggesting that it is possible to characterize the entire process of astrocyte reprogramming by combining these techniques.